Manajemen Sejarah Berbasis Komunitas: Pengembangan Kawasan Kauman sebagai Living Museum - Nur Aini Setiawati (Faculty of Cultural Sciences, 2018)
One of the community services developed by the Faculty of Cultural Sciences provides an assistance to the community of Kauman village in preparation for Kauman village development as Yogyakarta living museum. In this case, Kauman area will serve as a kind of village that has a sustainable cultural tradition since the founding of Ngayogyokarto Hadiningrat Sultanate. In accordance with the concept of the living museum, many kinds of ideas will be implemented to regain the old cultural traditions that were taken from interviews with Kauman elders, community fgures, and young people about the history of Kampung Kauman. Te interviews are basically an intangible heritage which its narrative was attached to the landscape of Kauman village. Te results obtained from the interviews is a collective memory of Kauman village society to the development history of Kauman village. Te compilation and determination of the location, the building, the narrative house of historical formation, and the tradition that is carried out regularly in one year is the initial basis for the implementation of the historical living museum.